PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA QUIZIZZ TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SDN TIDUNG KOTA MAKASSAR - Mirnawati; Maruf; Amri Amal (STKIP Subang, 2025)
study aims to determine the effect of the Problem Based Learning (PBL) model assisted by Quizizz media on fourth-grade students’ learning outcomes in Integrated Science and Social Studies (IPAS) at SDN Tidung. This research used a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. The experimental class was taught using the PBL model with Quizizz media, while the control class used conventional learning methods. Data were collected through pretest and posttest assessments and analyzed using the Mann–Whitney U test at a 0.05 significance level. The results showed that the average posttest score of the experimental class was 79.40 with 90% mastery, while the control class scored 63.40 with 30% mastery. The statistical test obtained an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference between the two groups. These findings suggest that the PBL model assisted by Quizizz media positively influences students’ learning outcomes by creating an active, interactive, and enjoyable learning atmosphere. Therefore, the combination of PBL and Quizizz is effective in improving IPAS learning outcomes and can serve as an innovative learning alternative in elementary education.